RECENT GEODYNAMICS AND SEISMICITY OF THE FAR EAST AND THE EASTERN SIBERIA - Victor G. Bykov; Alexei N. Didenko; Tat’yana V. Merkulova (Геодинамика и тектонофизика, 2015)
The information on the «Problems of seismicity and recent geodynamics of the Far East and Eastern Siberia» Symposium is presented. It was held on June 1–4, 2010 at the Yu.A. Kosygin Institute of tectonics and teophysics, Far Eastern branch, Russian academy of sciences, Khabarovsk. The scope of plenary meetings, sessions and round-table discussions conducted during the Symposium is presented with a brief review of the most interesting scientific reports.